Eksistensi Tradisi Mappatettong Bola Masyarakat Di Desa Kiru Kiru Kecamatan Soppeng Riaja - Mrs. Darmawati; Mrs. Nurlela (Rayhan Intermedia, 2023)
This research aims to determine the function of the values contained in the mappatettong bola tradition on the Kiru-kiru village community in maintaining social harmony in the global era, and to find out the meaning of mappatettong bola in the Kiru-kiru village regarding the importance of maintaining the mappatettong bola tradition. To find out the application of the mappatettong bola tradition in maintaining community relations in Kiru-Kiru village. Bugis society has a main part, namely kinship relations and togetherness which is considered very important in a form of society. One of these parts in Bugis is the existence of a tradition of mutual cooperation in Bugis society. This custom is very closely related to the spirit of togetherness and solidarity in society. The difference between the Mappatettong Bola tradition and other villages is that the Bugis tribe community in Kiru-kiru village likes to work together, especially in the work of building Bugis houses or stilt houses. The nature of mutual cooperation possessed by the Kiru-Kiru village community is one of the characteristics of rural communities in maintaining their cultural values, especially in facing the era of globalization.